Práticas de responsabilidade social empresarial e mudanças no ambiente institucional: estudo de caso no setor citrícola paulista - Sousa, Leila Araújo de (Universidade Federal de São Carlos, 2006)
In the last decade there has been a growth on society concern with topics related to epics, citizenship, human rights, economic development and social belonging. In this sense, all kinds of organizations are more and more worried on reaching and showing performance related to environment protection, socially and economically correct, controlling the impacts of its relations, processes, products and services in society according to its politics and its social responsibility goals. However, many doubts concerning what really is socially responsible in practical application, therefore in its speech. Although there has been indicators that point to the industries mentality and posture change related to its engagement in the social space. The reasons which promoted it are still doubtful. Probably this reasons must achieve specific shaping in specific realities as well, so the importance of the study: a contributions on the comprehension as how the industrial social responsibility is configured in the Sao Paulo´s orange-juice complex. Thus, the objective of this work is to design a framework of industrial social responsibility in the citric section of the São Paulo State and therefore there has been developed a case study of three different important agents in this reproductive chain. Throughout this study there is a search to build up an analysis in the comprehension of this issues on what concerns to be socially responsible, approaching and existent dynamic in the sector environmental institution that reinforces the adoption and the restructuring of acts related to industrial social responsibility. As a result it has been notice that the socially responsible acts are acts which has been an adaptation from pressure received by each agent, as well as they are isomorphic within each segment since it can be verified the existence of realities, power and legitimacy very different among the agents. It has also been noticed that the activities has been well accepted by human resources professionals and that the industrial social responsibility has been taken as a management tool.
Keywords: Responsabilidade social da empresa; Setor citrícola; Novo institucionalismo; Social responsibility; Industrial social responsibility; New institutionalism; Citric section; ENGENHARIAS::ENGENHARIA DE PRODUCAO